Web-based visualisation techniques for reporting zoonotic outbreaks - Ncube, Sinini Paul (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
Zoonotic diseases are diseases that are transmitted from animals or vectors to humans and vice versa. The public together with veterinarian authorities should readily access disease information as it is vital in rapidly controlling resultant zoonotic outbreak threats through improved awareness. Currently, the reporting of disease information in South Africa is predominantly limited to traditional methods of Information Communication Technologies (ICTs) like faxes, monthly newspaper reports, radios, phones and televisions. Although these are effective ways of communication, their disadvantage is that the information that most of them offer can only be accessed at specific times during a crisis. New technologies like the internet have become the most efficient way of distributing information in near-real-time. Many developed countries have used web-based reporting platforms to deliver timely information through temporal and geographic visualisation techniques. There has been an attempt in the use of web-based reporting in South Africa but most of these sites are characterised by heavy text which makes them time consuming to use or maintain. As a result most sites have not been updated or have ceased to exist because of the work load involved. The success of web reporting mechanisms in developed countries offers evidence that web-based reporting systems when appropriately visualised can improve the easy understanding of information and efficiency in the analysis of that data. In this thesis, a web-based reporting prototype was proposed after gathering information from different sources: literature related to disease reporting and the visualisation of infectious diseases; the exploration of the currently deployed web systems; and the investigation of user requirements from relevant parties. The proposed prototype system was then developed using Adobe Flash tools, Java and MySQL languages. A focus group then reviewed the developed system to ascertain that the relevant requirements had been incorporated and to obtain additional ideas about the system. This led to the proposal of a new prototype system that can be used by the authorities concerned as a plan to develop a fully functional disease reporting system for South Africa.
Keywords: Zoonoses -- Reporting; Communicable diseases -- Reporting; Communication in medicine; Medical telematics; Internet; Information visualization